Application of universal design in Malaysia: KAED universal design as research and training provider for Malaysia - Abdul Rahim, Asiah (IIUM Press, 2016)
The objective of this paper is to give the overview about the present status of the facilities, awareness and research related to Universal Design in Malaysia since its independence in 1957. For the last 10 years, Malaysia has shown exponential growth in every aspect, and the government of Malaysia has given a lot of support towards attending to the needs of the disadvantaged groups including women, children, single parents, the aged and the disabled. Many standards, regulations, code of practice and guidelines have been developed to have good accessibility, connectivity, usability and seamlessness in built environment. Recently, various groups, including professionals in the built environment such as architects, planners and engineers, academicians, officers from local authorities, developers and contractors have implemented accessibility and universal design in their projects and development. However, more effort from various bodies, be it government, non-government or higher-learning institutions, are still needed to transform Malaysia into a developed, safe and accessible country. Every year, the numbers of aged population are increasing, and the need to provide accessible facilities in Malaysia keeps getting higher to accommodate them. KAED Universal Design Unit (KUDU) of International Islamic University Malaysia was formed with the intention to promote the application of universal design in the built environment and product design, as well as to disseminate research findings through international conferences, symposiums, workshops and product competitions. KUDU also aims to improve the quality of life for the general public through promotion and implementation of universal design in the built environment. Research collaborations have also been conducted with other universities, locally and abroad. An elective subject related to universal design named Barrier Free Architecture was offered in the Bachelor of Architecture programme and Bachelor of Landscape Architecture programme starting 2008, in order to promote this approach.